Analisis Kebutuhan Awal untuk Pengembangan Buku Ajar Berbasis Budaya Kalimantan Barat Untuk Meningkatkan Literasi Kimia dan Kesadaran Budaya - Siti Aisyah; Baiq Miftah Azumi; Siti Nurul Yaqutu Burhani; Mifta Hurrahman (Postgraduate, University of Mataram, 2025)
The limited implementation of chemical literacy and culture-based learning in schools has hindered the development of students’ critical thinking and cultural appreciation. This study aims to identify the initial needs for developing a culture-based electronic chemistry textbook grounded in the local traditions of West Kalimantan. A descriptive quantitative method was employed, involving 11 chemistry teachers from schools implementing the Merdeka Curriculum. Data were collected through questionnaires and supported by an extensive literature review. The questionnaire data were analyzed using descriptive statistics, while literature was analyzed qualitatively. The results showed that 54.54% of teachers had not implemented chemical literacy-based learning, and 90.90% had never applied culture-based approaches. Most teachers used government-issued textbooks and encountered challenges in integrating chemistry content with local culture due to limited references. Student characteristics also indicated a need for interactive and contextual teaching materials that align with diverse learning styles and cognitive development stages. In addition, the cultural analysis revealed that thermochemistry concepts can be meaningfully linked to local practices in West Kalimantan. Therefore, the development of a culture-based electronic chemistry textbook is essential to enhance students’ chemical literacy and cultural awareness through relevant, contextual, and meaningful learning experiences